Role of pediatrician in formation of reproductive health in children and teenagers - T. V. Otpuschennikova; L. A. Derjugina; I. V. Goremykin (Лечащий Врач, 2021)
We considered diseases of sexual system in boys which threaten their reproductive health, the role of urinary tract infections in children and teenagers in formation of infertility, urination disorders. The methods of examination and tactics in conducting such patients were discussed.